2017
DOI: 10.1037/rep0000174
|View full text |Cite
|
Sign up to set email alerts
|

Using the NIH Toolbox Cognition Battery (NIHTB-CB) in individuals with traumatic brain injury.

Abstract: Findings provide evidence of construct validity and the clinical utility of the NIHTB-CB in individuals with TBI. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 62 publications
2
44
0
Order By: Relevance
“…For individuals with acquired brain injury, the Crystallized Cognition Composite Score can serve as an estimate of pre-injury general cognitive ability. This composite correlates strongly with other known “hold” tests (Gershon et al, 2014) and is resistant to the effects of TBI (Tulsky et al, under review). The fluid cognition tests are List Sorting Working Memory, Picture Sequence Memory, Pattern Comparison Processing Speed, Flanker Inhibitory Control and Attention Test (measuring both attention and executive functioning), and the Dimensional Change Card Sort Test.…”
Section: Methodsmentioning
confidence: 63%
See 3 more Smart Citations
“…For individuals with acquired brain injury, the Crystallized Cognition Composite Score can serve as an estimate of pre-injury general cognitive ability. This composite correlates strongly with other known “hold” tests (Gershon et al, 2014) and is resistant to the effects of TBI (Tulsky et al, under review). The fluid cognition tests are List Sorting Working Memory, Picture Sequence Memory, Pattern Comparison Processing Speed, Flanker Inhibitory Control and Attention Test (measuring both attention and executive functioning), and the Dimensional Change Card Sort Test.…”
Section: Methodsmentioning
confidence: 63%
“…This study provides validity evidence for the NIHTB-CB in TBI. Another study involving the same samples reported significant group differences between people with and without TBI, and illustrated that performance on the NIHTB-CB is associated with injury severity (Tulsky et al, under review). The present study adds two important findings.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Four tests were chosen were used as a brief neuropsychological tests battery to assess memory and speed functions. NIH Toolbox tests have excellent reliability and validity as reported by Tulsky et al (2017). Before the 2016 season, the Toolbox testing platform was changed from a desk-top computer to an iPad.…”
Section: Nih Toolboxmentioning
confidence: 99%